2015
DOI: 10.1074/jbc.m115.676700
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Deletion of Fat Storage-inducing Transmembrane Protein 2 (FIT2/FITM2) Causes Lethal Enteropathy

Abstract: Background: FIT2 is an ER protein implicated in regulating cytosolic LD formation in mammals. Results: FIT2 deficiency in an inducible whole body knock-out mouse model leads to lethal enteropathy. Conclusion: FIT2 is required for normal intestinal homeostasis and survival. Significance: This study provides evidence that FIT2 is essential for murine intestinal health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 66 publications
4
46
0
Order By: Relevance
“…Miranda et al found that mice with adipose‐specific FIT2 deficiency developed severe, progressive lipodystrophy with fatty liver, tissue macrophage infiltration, and insulin resistance, with few but abnormally large lipid droplets on histology. Goh et al found that whole‐body FIT2 knockout mice developed lethal enteropathy with death from severe fat malabsorption occurring within weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Miranda et al found that mice with adipose‐specific FIT2 deficiency developed severe, progressive lipodystrophy with fatty liver, tissue macrophage infiltration, and insulin resistance, with few but abnormally large lipid droplets on histology. Goh et al found that whole‐body FIT2 knockout mice developed lethal enteropathy with death from severe fat malabsorption occurring within weeks.…”
Section: Discussionmentioning
confidence: 99%
“…FIT2 knockdown in zebrafish prevents diet-induced CLD accumulation in enterocytes, as demonstrated by reduced neutral lipid staining after high fat feeding compared to wild-type zebrafish. More recently, a whole body postnatal FIT2-deficient mouse model was generated and found to lack CLDs in enterocytes in response to a dietary fat challenge [135]. Interestingly, these mice have similar postprandial triglyceridemic response and enterocyte TAG content as TAG accumulates in the ER.…”
Section: Chylomicron (Cm) and Cytoplasmic Lipid Droplet (Cld) Syntmentioning
confidence: 99%
“…Interestingly, these mice have similar postprandial triglyceridemic response and enterocyte TAG content as TAG accumulates in the ER. Surprisingly, intestinal epithelial cell specific FIT2-deficient mice have normal enterocyte CLD storage and secretion, suggesting that FIT2 in cells other than enterocytes is crucial for enterocyte CLD accumulation [135]. These results are surprising in light of the ability of FIT2 to bind directly to TAG, but suggest that FIT2 may also have the ability to regulate enterocyte CLD storage through an indirect mechanism.…”
Section: Chylomicron (Cm) and Cytoplasmic Lipid Droplet (Cld) Syntmentioning
confidence: 99%
“…Postnatal deletion of FIT2 in the mouse is lethal. Upon acute oil feeding, neutral lipids within enterocytes in these animals accumulate in the ER and fail to make droplets for TG storage [72]. …”
Section: Fit2mentioning
confidence: 99%